Một số vấn đề lí luận về phát triển đội ngũ giảng viên trong lực lượng Công an nhân dân theo hướng tiếp cận năng lực - Nguyễn Thị Hồng Nhung, Nguyễn Thị Hồng Nhung (Tạp chí Giáo dục, 2026)
In the context of educational reform and digital transformation, developing the faculty in the People’s Public Security higher education institutions through a competency-based approach has become an imperative requirement to meet the demands of training and building the force in the new era. The competency-based approach emphasizes professional qualities, skills, and knowledge linked to practical duties, while also reflecting a shift in management and training perspectives in modern education. This article analyzes the theoretical foundations, clarifies the characteristics of the faculty in the People’s Public Security institutions, and identifies influencing factors at the individual, institutional, and external levels. On this basis, it proposes key directions for faculty development, including planning, recruitment, utilization, training and professional development, evaluation, as well as creating supportive environments and work motivation. The ultimate goal is to enhance the quality of teaching human resources, thereby contributing to the construction of a modern, professional, elite, and strong People’s Public Security force.